Gain-Scheduled Sliding Mode Control with Time-Delay Estimation for a Cable-Driven Joint of an Underwater Manipulator - Xiaopeng Lv; Yuqi Qiao; Qifeng Zhang; Yunfei Bai; Qingfeng Yao (Journal of Marine Science and Engineering, 2026)
Using cable transmission in underwater manipulators helps to reduce the mass and rotational inertia of distal moving components, but the control performance of cable-driven joints is affected by flexible cable transmission, equivalent joint-side friction, hydrodynamic effects, and external disturbances. This paper proposes a control method combining time-delay estimation (TDE) with gain-scheduled sliding mode control (GSMC) for a cable-driven joint of an underwater manipulator. TDE uses delayed control-input and joint-acceleration data to estimate and compensate for the lumped dynamic term in the equivalent joint model online. GSMC employs a composite sliding surface and an error-dependent gain-scheduling mechanism to suppress trajectory-tracking errors in the presence of the TDE estimation residual. In joint-level MATLAB/Simulink R2024b simulations, smooth-step, sinusoidal-trajectory-tracking, and ablation results under predefined combined-uncertainty conditions, together with the results of 50 paired Monte Carlo runs, show that TDE-GSMC achieves the lowest major tracking-error indices among the four methods for the smooth-step and 0.35Hz sinusoidal trajectories and also yields the lowest mean tracking error and 95th percentile of the disturbance peak in the Monte Carlo simulations; the ablation results further characterize the performance differences among the tested controller configurations.

Cost-minimizing alternative dosage regimens of imipenem/cilastatin/relebactam for patients with renal impairment: a pharmacokinetic/pharmacodynamic simulation study - Xiaoping Shi; Donghui Lao; Qing Xu; Xiaoyu Li; Bijue Liu; Qingfeng He; Xiao Zhu; Qianzhou Lv (European Journal of Clinical Pharmacology, 2026)

Downregulated miR-199a-3p in Preeclamptic Placenta-derived Exosomes from Cord Blood Hinders VEGF-induced Fetal Glomerular Dysplasia Through Inhibiting Akt1(S473) Phosphorylation via Targeting PHLPP2 - Xiaotong Jiang; Mengqi Gu; Yu Xie; Yuchen Li; Qingfeng Lv; Pengzheng Chen; Die Jing; Yu Zhou; Xietong Wang; Lei Li (Stem Cell Reviews and Reports, 2025)

Pure salt expansion behavior in sulfate saline soil under negative temperature conditions - Fengling Ji; Yuansheng Peng; Qingfeng Lv; Wei Li; Jingjing Yu (Cold Regions Science and Technology, 2024)

Construction of Remote Sensing Quantitative Model for Biomass of Deciduous Broad-Leaved Forest in Mazongling Nature Reserve Based on Machine Learning - Xuehai Tang; Dagui Yu; Haiyan Lv; Qiangxin Ou; Meiqin Xie; Peng Fan; Qingfeng Huang (Journal of the Indian Society of Remote Sensing, 2024)
As an important forest type, deciduous broad-leaved forest is crucial for estimating forest carbon sequestration capacity and evaluating forest carbon balance. This study focuses on the natural deciduous broad-leaved forest of Mazongling Nature Reserve in Jinzhai County of China. WorldView-2 images were selected as data source. 36 candidate factors including vegetation indices, texture features, and topographic factors were used for modelling. Three machine learning algorithms (i.e., random forest, k-nearest neighbor, and artificial neural network) were used to establish the optimal quantitative retrieval model for natural deciduous broad-leaved biomass. Results showed that the ANN model was the best predictor with R 2 = 0.69 and RMSE = 31.53 (Mg·ha −1 ). Combining the ANN model with the complete spatial coverage of remote sensing data, we developed a distribution map of natural deciduous broad-leaved biomass in the Mazongling forest farm. The estimated average biomass of the study area was 90.34 ± 47.96 Mg·ha −1 . In addition, the influence of light saturation on model accuracy is also discussed. This study confirms that remote sensing data in temporal and spatial space can improve the model estimation accuracy.

Benthic foraminiferal assemblages in the coastal zone of the yellow river delta: Environmental significance and characteristics of microbial diversity - Shuyang Huang; Qing Li; Xiaohua Qiu; Hong You; Ruimin Lv; Wei Liu; Qingfeng Chen; Tiantian Wang; Jing Zhang; Junjian Ma; Zihao Wang; Shigang Ding (Continental Shelf Research, 2024)

2.5 V “water in salt” aqueous micro-supercapacitors based on polypyrrole-coated NiCo layered double hydroxides - Xijuan Li; Xukun Wang; Guo Liu; Xinyi Sui; Qingfeng Wu; Xinge Wang; Xueliang Lv; Erqing Xie; Zhengxing Zhang (Chemical Engineering Journal, 2023)

Susceptibility assessment of soil erosion in overlaying diluvial fan of shallow underground pipelines - Qingdong Wang; Yingbin Zhang; Qingfeng Lv; Chenlin Xiang; Xiao Xia; Jing Liu (Bulletin of Engineering Geology and the Environment, 2021)
Soil erosion is a serious hazards occurring in overlaying diluvial fans of shallow underground pipelines. To learn the extent of soil erosion in such landforms, we propose a method of susceptibility assessment of soil erosion based on a case study of the Chaka diluvial fan, Qinghai Province, China. First, we conducted a field investigation at 24 sites, to obtain the land surface properties. Then, vital information such as soil anti-scouribility, permeability, density, sectional water volume, and pipeline burial depth was collected. The slope grade and the vegetation index were determined with the geographic information system (GIS) technology. Further, the analytic hierarchy process (AHP) was used to determine the weight of various indices on the potential susceptibility of shallow underground pipelines. The susceptibility classification of the study area soil erosion was obtained based on the GIS overlay analysis tool. Lastly, the susceptibility classification was compared with the results of the field investigation. Their consistency indicates that the proposed method can be successfully implemented to accurately assess soil erosion. The erosion mechanism indicates that occlusion and cementation have an important influence on the susceptibility intensity in overlaying diluvial fans of shallow underground pipelines.

Water stability mechanism of silicification grouted loess - Qingfeng Lv; Shengxin Wang; Dekai Wang; Zhumin Wu (Bulletin of Engineering Geology and the Environment, 2014)

Overexpressed mutant optineurin(E50K) induces retinal ganglion cells apoptosis via the mitochondrial pathway - Qingfeng Meng; Jia Lv; Hongyan Ge; Lu Zhang; Fei Xue; Yuanmao Zhu; Ping Liu (Molecular Biology Reports, 2012)